Experimental investigation on electrical discharge machining of steel H13. (2021) - Mohanty, Rajesh Kumar; Saini, Surendra Kumar
Abstract: Electrical Discharge Machining (EDM) is being used to machine components made out of hard alloys and are geometrically complex in shapes. Different types of materials like tool steels, composites, carbides and super alloys are difficult to machine by conventional machining process can be machined by EDM. But this process still has some limitations during machining of hard alloys like tool steel (H13). This material finds application in various types of industries such as tool and die, nuclear and aerospace etc. In this research paper, simultaneous optimization of output parameters over cut and material removal rate is done using desirability approach. Orthogonal array (L18) design was used to perform the EDM experiment on H 13 steel.